Монгол цэрэг Чосөнъ улсыг дайлахад оролцсон нь: A Study on Mongolian Troops in the Later Jin and Qing Invasions of Joseon - Ts., Tserendorj (Mongolian Journal of Foreign Languages and Cultures, 2023)
In the the first half of the 17th century Jurchens (or Manchu) invaded Korea's Joseon dynasty two times, in 1627 and 1636. Mongol troops took part in these invasions as an ally against Joseon. In this paper, we have tried to make clear some issues such as the participants who led the Mongoian troops and role of the Mongols in the invasions of Joseon.